Anomalous Hall effect in Cu doped Bi2Te3 topological insulator. (5th May 2020) - Singh, Abhishek; Kumar, Shiv; Singh, Mahima; Singh, Prajyoti; Singh, Rahul; Gangwar, Vinod K; Lakhani, Archana; Patil, Swapnil; Schwier, Eike F; Matsumura, Takeshi; Shimada, K; Ghosh, A K; et al.
Abstract: The angle resolved photo-emission spectroscopy (ARPES) study and magneto-transport properties of Bi2 Cu x Te3− x have been investigated. ARPES study indicates the clear existence of surface states in the as-prepared samples. The estimated bandgap from ARPES is found to be ∼5 meV and 16 meV respectively for x = 0.03 and x = 0.15 samples. Presence of larger Cu concentration ( x = 0.15) introduces magnetic ordering. Observed non-linearity in the Hall data is due to the existence of anomalous Hall effect which can be attributed to the 2D transport. The observed magneto-transport features might be related to the surface carriers which is confirmed by ARPES study.